Penanaman Kembali dan Pembuatan Papan Indikasi pada Taman di Perumahan Tiban Ayu - Andry, Andry; Derista, Elva; Hendie, Hendie; Hendrik, Hendrik; Jeckie, Jeckie; Boy, Michael God; Wiliam, Wiliam; Vernando, Wilson; Wati, Yeni (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2019)
The purposes of this society's dedication are to increase public awareness towards beauty and healthy environment, to build and increase the sense of togetherness on preserving the environment to achieve a better & healthier lifestyle. The first step of implementation is to observe the environment and acquire some information about the problem that exists in the environment. Second, discuss the best solution with the public figure and apply it to the environment. Last, to implement the solution that already been discussed. After the implementation, we found that the community was very enthusiastic to participate in preserving their living environment and we do take this action as a successful society dedication.